Book Review: Derek Pardue, Cape Verde, Let's Go: Creole Rappers and Citizenship in Portugal. (26th March 2018) - Harte, Colin
Abstract : Derek Pardue. 2015. Cape Verde, Let's Go: Creole Rappers and Citizenship in Portugal. Chicago: University of Illinois Press. 192pp. ISBN 978-0-252-08117-0 (pbk). 25